Resuscitation orders in acute hospitals: A point prevalence study. (19th October 2016) - Mills, Amber; Walker, Anne; Levinson, Michele; Hutchinson, Alison M; Stephenson, Gemma; Gellie, Anthea; Heriot, George; Newnham, Harvey; Robertson, Megan
Abstract : Objective: To determine the prevalence of resuscitation orders and Advance Care Plans, and the relationship with Medical Emergency Team (MET) calls. Methods: A point prevalence review of patient records at five Victorian hospital services. Results: One thousand nine hundred and thirty‐four patient records were reviewed, and 230 resuscitation orders and 15 Advance Care Plans found. Significantly, more resuscitation orders were found at public hospitals. Patients admitted to private hospitals were older, with shorter admissions. A further 24 orders were written following MET calls for 97 patients. Only 16% of patients aged 80+ years had a resuscitation order written within 24 hours of admission. Conclusion: Fewer resuscitation orders were written at admission for older adults than might be expected if goals of care and resuscitation outcome are considered. MET continue to have a prominent role in end‐of‐life care. Consideration and documentation about treatment plans are needed early in an admission to avoid burdensome and futile resuscitation events.